The Link Between Memory, Narrative and Empathy in Teaching Difficult Knowledge in Holocaust Education - Shalom, Maya; Gross, Zehavit (Frontiers in Education, 2022)
Research has shown that the use of first-person narrative can foster a high level of identification, empathy, and an increase in memory. However, little is known about the effect of first-person narrative in the teaching of difficult knowledge. In this study, we examine how pre-service teachers (PSTs) (N=55) process difficult knowledge presented in a first-person narrative and a third-person narrative film, using behavioral measures of empathy, level of previous knowledge and of short-term and long-term memory. What was surprising about the findings in this study was that the third-person narrative film contributed to a higher performance in both short-term and long-term memory compared to the first-person narrative film.